THE IMPLEMENTATION OF PARENTING EDUCATION PROGRAM FOR THE STUDENTS’ PARENT TO SUPPORT THE CHILD-FRIENDLY EDUCATION IN ELEMENTARY SCHOOL - Zulfin Rachma Mufidah (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2018)
This study is about the importance of parenting education to give knowledge, understanding, and skills for both parents and the teachers in educating, guiding, parenting, and organizing the education provided by parents at home and children-friendly education at school. The purposes of this study as follows, to describe the process of implementation in parenting education program, to describe the process of evaluation in parenting education program, and describe the result of parenting education program. The subjects of this study are Ar-Rahman Darul Ilmi Elementary School teachers, and parents of the third-grade students who are involved in the implementation of parenting education program.  The data collection techniques were conducted by observation, interview, and documentation. The result of the study shows that: 1) the concept of parenting education program activities include the setting of time, place of implementation, media, and the facilities of school used in the implementation of parenting conducted by the administrators and teachers. 2) The implementation of the parenting education program is formed by the meetings of the parents while the discussion is prioritizing on how to educate by preceding the right of children in learning. 3) Socializing child-friendly learning media which can be used to guide the children. 3) Evaluating the parenting program by using interview method based on the material which has been given in parenting education program. 4) The result of child-friendly manner at home and school. 5) The continuity of child-friendly parenting education program which will be applied on an annual basis.